Macro and Micro Mineral Composition of Haruan Fish (Channa striata) in Banjar District, South Kalimantan - Rahmat Yunus; Dahlena Ariyani; Muhammad Aisy (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Minerals have an essential role in the human body. Information about the mineral content of haruan fish in Banjar Regency is very limited. This research aimed to determine the mineral compound of haruan fish originally from ponds in Banjar Regency. Pond-sourced fish samples were processed until they became powders. The ash compound of haruan fish powder was calculated using the gravimetric method. The mineral compound was analyzed using an XRF spectrometer. Wild haruan fish contained 98.85% macro minerals, with the mineral composition of 14.4% P (10.2 mg/kg), 19.9% Ca (19,9 mg/kg), 60.6% K (42.5 mg/kg), and 0.85% S (0.6 mg/kg). Farmed haruan fish contained 94,76% macro minerals, consisting of 15.6% P (12.9 mg/kg), 17.2% Ca (14.3 mg/kg), 61.1% K (50.8 mg/kg), and 0.86% S (0.7 mg/kg). Wild haruan contained 3.51% micro minerals, consisting of 4.44% Fe (3.7 mg/kg), 0.10% Cu (0.08 mg/kg), and 0.22% Zn (0.18 mg/kg). Farmed haruan contained 4.76% micro minerals, consisting of 4.44% Fe (3.7 mg/kg), 0.10% Cu (0.08 mg/kg), and 0.22% Zn (0.18 mg/kg). Wild haruan fish contained 0.56% trace element, 0.46% Rb (0.32 mg/kg), and 0.1% Re (0.07 mg/kg). Farmed haruan fish contained 0.42% trace element, 0.34% Rb (0.28 mg/kg), and 0.08% Re (0.06 mg/kg).